PERGESERAN MAKNA NIKAH MENURUT ISLAM DALAM FENOMENA PERKAWINAN DINI DI INDONESIA: PENDEKATAN DRAMATURGI ERVING GOFFMAN - Asy-Syifa, Ahna Firzana; Pratiwi, Diajeng Annisaa; Muniiroh, Af’idatul (MAMBA'UL 'ULUM, 2025)
This study aims to analyze the shifting meaning of marriage in the phenomenon of early marriage in Indonesia from an Islamic perspective using Erving Goffman’s dramaturgical theory. In Islamic teaching, marriage is a sacred covenant intended to achieve tranquility (sakinah), love (mawaddah), and compassion (rahmah). However, in modern social reality, marriage—especially early marriage—often shifts from a spiritual act of worship to a symbolic performance used to gain social recognition and moral legitimacy. This research employs a qualitative descriptive method with a symbolic interactionism approach, using library research as the main technique for data collection. Data are obtained from scientific journals, books, and official reports related to Islamic law, sociology, and cultural studies. The findings reveal that early marriage functions as a “social performance,” where individuals and families project piety and honor on the front stage while concealing emotional, economic, and spiritual immaturity in the backstage. The study concludes that this shift represents a change from theological meaning to symbolic religiosity. It highlights the importance of restoring marriage to its genuine Islamic values—as an act of worship and moral responsibility—to build harmonious and sustainable families.